2021
DOI: 10.1371/journal.pone.0258634
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated fetal growth velocity across the third trimester is associated with increased shoulder dystocia risk among fetuses who are not large-for-gestational-age: A prospective observational cohort study

Abstract: Objective To investigate whether fetuses with accelerated third trimester growth velocity are at increased risk of shoulder dystocia, even when they are not large-for-gestational-age (LGA; estimated fetal weight (EFW) >95th centile). Methods Fetal growth velocity and birth outcome data were prospectively collected from 347 nulliparous women. Each had blinded ultrasound biometry performed at 28 and 36 weeks’ gestation. Change in EFW and abdominal circumference (AC) centiles between 28–36 weeks were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…EFW can help to take appropriate precautions and minimize harm. In the study of Mourad et al and also in the study of MacDonald T. et al it was shown that the risk of SD was higher in groups with high EFW [16,17].…”
Section: Discussionmentioning
confidence: 83%
“…EFW can help to take appropriate precautions and minimize harm. In the study of Mourad et al and also in the study of MacDonald T. et al it was shown that the risk of SD was higher in groups with high EFW [16,17].…”
Section: Discussionmentioning
confidence: 83%
“…In pregnant women, large babies are associated with prolonged labor and delivery, increased rates of vaginal obstruction and cesarean section, and a range of complications including postpartum hemorrhage. The fetus is also at increased risk for shoulder dystocia, brachial plexus injury, hypoglycemia, and even asphyxia, as well as for adult health status, including obesity and cardiovascular disease [ 4 , 5 , 27 ]. Therefore, early detection of high-risk pregnant women and timely pregnancy care and guidance are of great importance to prevent the development of huge babies and promote maternal and infant health.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of macrosomia varies greatly among different regions in China, averaging about 7%-9% [ 2 , 3 ]. Neonatal weight affects the delivery mode of pregnant women and can increase the risk of assisted delivery, dystocia, neonatal birth injury, birth canal injury, and other risks for vaginal delivery, as well as the incidence of neonatal asphyxia [ 4 , 5 ]. At present, the mechanism of macrosomia is not clear, and the occurrence of macrosomia is usually the result of multiple factors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Singleton pregnancies at the 36-week scan will be included because this study aims to provide evidence for a late pregnancy ultrasound screening strategy to prevent stillbirths, perinatal mortality and adverse neurodevelopmental outcomes. Although the gestational age widow constituting the 36-week scan varies,35–40 this study will include systematic reviews with obstetric scans from 34+0 weeks gestation. This study will not be limited to any context or language.…”
Section: Methodsmentioning
confidence: 99%